ANALISIS TINGKAT PERSAINGAN INDUSTRI PERBANKAN DI INDONESIA - Romauli Manurung (Quantitative Economics Journal, 2016)
This study aimed to analyze the structure of the banking industry and the level of competition of banking institutions in Indonesia. In measuring and analyzing the model used Panzar-Rosse built on indicators of competition, called H-Stats, which provide a quantitative assessment of the competitive nature of the market. H-statistics calculated from equation reduction in revenue and the size of the total revenue elasticity with respect to changes in input factor prices. Panzar and Rosse show that with certain assumptions, comparison of the static nature of the type of the equation provides a replacement for the overall level of competition prevailing in the market. By using secondary data issued by Bank Indonesia (BI), this study used pooled the data (data panel) is to combine data from year 2010 to 2014 on 9 banking institutions. The results showed that the level of competition in the Indonesian banking industry generally contain the elements of nature and the nature of the market monopoly of perfect competition or are in a situation of monopolistic competition (monopolistic competitions)